Biopsy‐proven case of Epstein–Barr virus (EBV)‐associated vasculitis of the central nervous system. Issue 3 (22nd December 2016) - Kano, Kohei; Katayama, Takayuki; Takeguchi, Shiori; Asanome, Asuka; Takahashi, Kae; Saito, Tsukasa; Sawada, Jun; Saito, Masato; Anei, Ryogo; Kamada, Kyousuke; Miyokawa, Naoyuki; Nishihara, Hiroshi; et al.
Abstract : A 75‐year‐old woman was admitted to our hospital with rapidly deteriorating consciousness disturbance. She had a 7‐year history of rheumatoid arthritis (RA), which had been treated with methotrexate (MTX) and prednisolone. Brain T2‐weighted MRI showed diffuse high‐intensity lesions in the cerebral subcortical and deep white matter, bilateral basal ganglia and thalamus. A cerebrospinal fluid examination revealed elevated protein levels and positive Epstein–Barr virus (EBV) DNA. Human immunodeficiency virus was negative. Brain biopsy showed perivascular lymphocytic infiltration in the parenchyma and meninx with EBV‐encoded small RNA (EBER). Since this case did not fulfill the criteria for chronic active EBV infection (CAEBV), she was diagnosed with Epstein–Barr virus (EBV)‐associated vasculitis of the central nervous system. High‐dose methylprednisolone, acyclovir, ganciclovir and foscarnet were not effective. Although EBV is a causative agent of infectious mononucleosis (IM), lymphomas and nasopharyngeal carcinomas, vasculitic pathology of the central nervous system with EBV reactivation in the elderly is rare. Immunosuppressive drugs such as steroids and MTX are widely used to treat autoimmune disorders, but may exacerbate the reactivation of EBV. This is the first case of biopsy‐proven EBV‐positive/HIV‐negative vasculitis during the treatment of RA with MTX and steroids. This case indicates that EBV‐associated vasculitis needs to be considered as a differential diagnosis of CNS vasculitis.